Peran dan Tantangan Tenaga Pendidik dalam Menghadapi Kurikulum Merdeka di SMP Negeri 2 Sipoholon - Sipahutar, Sonia Widia; Gita Sonya Sagala; Enjelina Aruan; Renimawati Gea (CV Putra Publisher, 2024)
The role and challenges faced by teaching staff in implementing the independent curriculum at Sipoholon State Middle School. In the learning process using the independent curriculum, teaching staff at SMP Negeri 2 Sipoholon have challenges, including: making clear and flexible schedules for teachers, holding regular training and workshops, forming teams or working groups of teachers, and encouraging active participation of students in the learning process. Solutions to face these challenges include increasing supervision and support from schools, regular training and workshops, as well as providing ongoing professional training and development. In this way, educators are expected to be able to overcome these challenges and improve student performance significantly. This research was conducted using qualitative methods, namely field observations and interviews. The results of the research show that the implementation of the independent curriculum at SMP Negeri 2 Sipoholon. The results of the research show that the implementation of the independent curriculum is less effective at SMP Negeri 2 Sipoholon because it causes many problems. The aim of this research is to identify the roles and challenges faced by teaching staff in implementing the independent curriculum at SMP Negeri 2 Sipoholon and to develop effective solutions to overcome these challenges. This research aims to provide an in-depth understanding of the important role of teaching staff in designing and implementing an independent curriculum, as well as to identify concrete obstacles that may hinder effective implementation.